Proposta de instrumento de triagem para disfagia em idosos com a síndrome da fragilidade - Santos, Beatriz Nayara Lopes dos (2024)
Objectives: I – Conduct a systematic review of observational studies to compile the main instruments for screening dysphagia in elderly individuals with Frailty Syndrome; II – Propose a screening tool for dysphagia in frail elderly patients, developed through a systematic review of the literature. Methods: I – Searchers were conducted in the databases PubMed, Web of Science, Scopus, Embase, and Google Scholar using descriptors that included the words Frailty, Deglutition Disorder, and Dysphagia, between June and July 2023, without time or language filters. Observational studies were included with a sample of participants aged 60 years or older, regardless of sex and ethnicity, as well as articles that descriptively addressed the instruments used for dysphagia screening in the frail elderly population. The methodological quality assessment was performed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies of the National Institutes of Health (NIH). II – The tool was developed by selecting the items that presented the highest incidence of presentation in the protocols obtained in the systematic review stage and theoretical-practical justification of application in the sample group studied. Results: I - Six articles met the proposed eligibility criteria and were included in the described systematic review. Three studies used the "10-Item Eating Assessment Tool (EAT-10)"; one study used the "Simple 4-point questionnaire test (4QT)"; one study used the "30-ml water swallow test"; and one study used the "Test of Mastication and Swallowing Solids (TOMASS)", as well as the "Timed Water Swallow Test (TWST)" and the "3-oz water swallow", each used by distinct authors in one study. II – The synthesis and analysis of the systematic review allowed the development of a screening prototype for dysphagia in elderly individuals with Frailty Syndrome, composed of two distinct domains: subjective assessment, consisting of eight (8) self-reported items and the water swallow test, based on the assessment of swallowing characteristics and the time required to ingest 30 ml of water. Conclusion: I – The results obtained reveal a significant gap in the national and international scientific literature regarding dysphagia screening for patients with frailty. This gap is characterized by the use of generic, often non-validated, or non-specific protocols for the geriatric condition under study. II – The presented protocol has the potential to assist in the screening and early identification of dysphagia in frail older adults across various healthcare settings, providing a viable, cost- effective, and multidisciplinary alternative for the early detection of swallowing disorders.